Manganese(II) Semiquinonato and Manganese(III) Catecholato Complexes with Tridentate Ligand: Modeling the Substrate‐Binding State of Manganese‐Dependent Catechol Dioxygenase and Reactivity with Molecular Oxygen. Issue 6 (19th March 2013) - Komatsuzaki, Hidehito; Shiota, Akihiko; Hazawa, Shogo; Itoh, Muneaki; Miyamura, Noriko; Miki, Nahomi; Takano, Yoichi; Nakazawa, Jun; Inagaki, Akiko; Akita, Munetaka; Hikichi, Shiro
<x xml:space="preserve">Abstract</x> Catecholate catwalk: Monomeric manganese(III) catecholato and manganese(II) semiquinonato complexes as the substrate‐binding model of catechol dioxygenase have been synthesized and structurally characterized. The semiquinonato complex reacted with molecular oxygen to give ring‐cleaved products and benzoquinone in the catalytic condition.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>